Connectedness through a strong form of TBLT, classroom implementation of the CEFR, cyclical learning, and learning-oriented assessment - O'Dwyer, Fergus; Imig, Alexander; Nagai, Noriko (Language learning in higher education (Berlin, Germany), 2014)
This paper, fundamentally a procedural paper, outlines pedagogical practices which others may want to adapt for their own purposes. We demonstrate how a strong form of task-based language learning and teaching (TBLT), classroom implementation of the CEFR, cyclical learning, and assessment fulfilling roles, such as informing the next learning stage, can be combined in a connected pedagogy. We place this pedagogy in a theoretical framework, which includes explaining: how tasks in a strong form of TBLT are authentically linked to each other; the potential of the scaled descriptors of the CEFR (Council of Europe 2001); possible phases of cyclical learning; and how classroom assessment can perform roles such as a decision making tool, a participatory pedagogical process, and informing the next learning task. We provide examples of pedagogical implementation and attempt to map this pedagogy to the theoretical framework above. We show how scaled descriptors from the CEFR are used to create clear and concrete descriptors for a course that implements a strong form of TBLT. The implementation of a learning cycle is explained in terms of how assessment is performed, and the roles it undertakes. The concluding discussion outlines our opinions on why the practices outlined in the paper can create pedagogical synergy and a positive classroom assessment culture.